Amplitude of fibrillatory wave correlates with long-term maintenance of sinus rhythm after ablation in persistent atrial fibrillation. (19th May 2022) - Luca, A; Baskaralingam, A; Mccann, A; Vesin, J-M; Pascale, P; Le Bloa, M; Herrera, C; Roten, L; Kuhne, M; Spies, F; Knecht, S; Sticherling, C; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Commission for Technology and Innovation (CTI), Switzerland Background: Amplitude of fibrillatory wave (fWA) on surface ECG is regarded as a predictor of ablation outcome for atrial fibrillation (AF). Purpose: We sought to investigate whether fWA and its changes during ablation predicts long-term maintenance of sinus rhythm (SR) after wide circumferential isolation of pulmonary veins (WPVI) in persistent AF (peAF). Methods: 41 patients (63±10 y, sustained AF 11±7 months) underwent a de-novo WPVI. A second WPVI was performed in patients with recurrent AF in order to provide complete PV disconnection. We defined "success" as patients who remained in SR after one or two procedures, and "failure" otherwise. 60-sec ECG signals devoid of QRST waves were recorded during the index ablation at baseline and at the end of ablation (end_WPVI, before cardioversion or conversion of AF into SR). fWA was computed on leads V1 and V6b (placed on the pts' back) as the average difference between the upper and lower envelope of atrial ECG signals. Results: Over a mean follow-up of 33±9 months, 30 patients remained free from AF (success group), while 11 patients had AF recurrence after 2 WPVIs (failure group). The clinical characteristics (e.g. age, body mass index, left atrial volume or duration in sustained AF) were similar between groups (p > 0.05). The success group displayed significantly higher fWA values at baseline and end_WPVI than that of the failure group (p<0.05, Panel A and B). No significant difference was found between baseline fWA values and those measured at end_WPVI (p > 0.05). Conclusion: As fWA is independent of PVs contribution, it is a marker of atrial body remodelling. Low fWA values identify patients with peAF unresponsive to WPVI.